Mother trees, altruistic fungi, and the perils of plant personification - Robinson, David G.; Ammer, Christian; Polle, Andrea; Bauhus, Jürgen; Aloni, Roni; Annighöfer, Peter; Baskin, Tobias I.; Blatt, Michael R.; Bolte, Andreas; Bugmann, Harald; Cohen, Jerry D.; Davies, Peter J.; et al. (Trends in plant science, 2024)
There are growing doubts about the true role of the common mycorrhizal networks (CMN or wood wide web) connecting the roots of trees in forests. We question the claims of a substantial carbon transfer from ‘mother trees’ to their offspring and nearby seedlings through the CMN. Recent reviews show that evidence for the ‘mother tree concept’ is inconclusive or absent. The origin of this concept seems to stem from a desire to humanize plant life but can lead to misunderstandings and false interpretations and may eventually harm rather than help the commendable cause of preserving forests. Two recent books serve as examples: The Hidden Life of Trees and Finding the Mother Tree.
Online verfügbar: 19. September 2023, Artikelversion: 3. January 2024
Gesehen am 15.11.2023